Influence of El Niño and La Niña on rainfall in São Bento do Una - Pernambuco, Brazil (Research, Society and Development, 2020)
The objective is to study the relationship between the rainfall indexes in the municipality of São Bento do Una - PE due to the action of the El Niño and La Niña weather phenomenon. Relating the intensity of these events to the current drought scenario in the municipality of São Bento do Una in the State of Pernambuco, aiming at its influences on the poultry sector. We used monthly and annual precipitation series, provided by the Pernambuco State Water and Climate Agency of the State of Pernambuco and the Northeast Development Superintendence, referring to isolated years of El Niño (2007, 2009, 2010, 2012 and 2013) and La Niña (1998, 1999, 2000, 2008). Regarding El Niño's performance, the years 2009, 2010 stand out, which registered 60% and 58.3% more precipitation than the normal climatological. The years 2007 and 2013 were considered normal and the year 2012 was considered very dry. In the years that La Niña was active, specifically in 2000 and 2008, there was an increase in rainfall rates of 28.5% and 27.2% respectively. In 2001, normal rainfall was recorded. In the years 1998 and 1999 it was considered as pluviometrically dry. In the municipality, the performance of the El Niño and La Niña phenomena did not influence increases or decreases in rainfall rates.